ADOLESCENTS’ PERCEPTIONS OF PEER INFLUENCE ON SEXUAL BEHAVIOUR IN NSUKKA EDUCATION ZONE, ENUGU STATE. - Ugwu, Festus A.; Ohuakanwa, Chijioke E. (African Journal of Social and Behavioural Sciences, 2025)
The study investigated the impact of peer groups on the sexual behaviours of secondary school adolescents in the Nsukka Education Zone in Enugu State. The design of the study was ex post facto research. The population comprised 11,205 secondary school adolescents in the education zone, while the sample was 230 SS II secondary school adolescents. Three research questions and a hypothesis guided the study. The instrument for data collection was a questionnaire titled “Impact of Peer Group on Sexual Behaviour of Secondary School Adolescents (IPGSBSSA). Data collected were analysed using mean and standard deviation for research questions and t-test statistics to test the hypothesis at a 0.05 level of significance. Results revealed that peer group has a great impact on the sexual behaviour of secondary school adolescents. Results also showed that location was impactful on the sexual behaviour of both urban and rural adolescent dwellers, though urban dwellers had a higher mean than their rural counterparts. Among the strategies adopted to reduce the impact of peer groups on the sexual behaviour of both urban and rural dwelling adolescent secondary school students, factors such as promoting positive societal norms and values, older generation as role models, laying emphasis on good virtues, provision of guidance and counselling services for secondary school adolescents were impactful. Based on the findings, it was recommended that parents, teachers, and all those interested in the education industry should be responsive in their expected duties of guiding adolescents accordingly. Moreover, there is a need to replicate the study in other education zones and use larger samples to create room for result generalization.